Competency-Based Assessment of English Learning Outcomes: Theoretical Foundations, Practical Applications, and Solutions for Higher Education in Vietnam - Huyen, Duong Thi Thu; Hung, Le Ngoc (VNU Journal of Science: Education Research; Vol 41 No 3DO - 10.25073/2588-1159/vnuer.5279, 2025)
This research focuses on the suspicions and implementations of Competency-Based Assessment (CBA) in English teaching practices at a tertiary level in Vietnam, highlighting the limitations of traditional Knowledge-Based Assessment (KBA) which prioritizes retention over functional language usage. The investigation focuses on task, performance, portfolio, and digital-assisted formative assessment under the direction of constructivism, experiential learning theory, and formative evaluation theory. Despite the official endorsement, adopting CBA in Vietnam faces difficulties such as overreliance on summative assessment, poor standardization, unqualified teaching personnel, and technological inadequacy. The study proposes the “Research & Development & Benefit- R&D and B” paradigm to address such problems with R&D approaches using procedures, some tools for practice, and computer feedback to aid language development. It argues that moving from an evaluative focus on knowledge to one of competence is critical in improving English skills and responsiveness to international educational standards. This research improves students’ assessment processes and systems to ensure learners attain their academic goals while developing the necessary language skills for use in professional and academic settings.